Co-colonization of different species harboring KPC or NDM carbapenemase in the same host gut: insight of resistance evolution by horizontal gene transfer - Ji, Jingshu; Zhu, Yufeng; Zhao, Feng; Zhang, Jingjing; Yao, Bingyan; Zhu, Mingli; Yu, Yunsong; Zhang, Jun; Fu, Ying (Frontiers in Microbiology, 2024)
The dissemination of carbapenem-resistant Enterobacteriales (CRE) in nosocomial settings is primarily associated with the horizontal transfer of plasmids. However, limited research has focused on the in-host transferability of carbapenem resistance. In this study, ten isolates were collected from gut specimens of five individuals, each hosting two different species, including Escherichia coli, Klebsiella pneumoniae, Klebsiella aerogenes, Enterobacter cloacae, or Citrobacter koseri. Species identification and antimicrobial susceptibility were determined by MALDI-TOF MS and broth microdilution method.Carbapenemase genes were detected and localized using PCR, S1-PFGE and southern blot.The transferability of carbapenemase genes between species was investigated through filter mating experiments, and the genetic contexts of the plasmids were analyzed using whole genome sequencing. Our results revealed that each of the ten isolates harbored a carbapenemase gene, including blaNDM-5, blaNDM-1, or blaKPC-2, on a plasmid. Five different plasmids were successfully transferred to recipient cells of E. coli, K. pneumoniae or A. baumannii by transconjugation. The genetic contexts of the carbapenemase gene were remarkably similar between the two CRE isolates from each individual. This study highlights the potential for interspecies plasmid transmission in human gut, emphasizing the colonization of CRE as a significant risk factor for the dissemination of carbapenemase genes within the host. These findings underscore the need for appropriate intestinal CRE screening and colonization prevention.